2022
DOI: 10.22541/au.166325658.84625800/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Conserved transcriptional programming across sex and species after peripheral nerve injury predicts treatments for neuropathic pain

Abstract: Background and Purpose: Chronic pain is a devastating problem affecting 1 in 5 individuals around the globe, with neuropathic pain the most debilitating and poorly treated type of chronic pain. Advances in transcriptomics and data mining have contributed to cataloging diverse cellular pathways and transcriptomic alterations in response to peripheral nerve injury but have focused on phenomenology and classifying transcriptomic responses. Experimental approach: Here, with the goal of identifying new types of pai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…4 Furthermore, Gpr160 is upregulated in the spinal cord in both male and female mice and rats that underwent spared nerve injury. 31 In addition to animal models of neuropathic pain, Gpr160 is also expressed in patients with neuropathic pain. Indeed, a recent study identified Gpr160 as one of the top pain-associated genes upregulated in the dorsal root ganglion in a cohort of female patients with neuropathic pain who underwent thoracic vertebrectomy surgery for spinal reconstruction or tumor resection.…”
Section: Introductionmentioning
confidence: 99%
“…4 Furthermore, Gpr160 is upregulated in the spinal cord in both male and female mice and rats that underwent spared nerve injury. 31 In addition to animal models of neuropathic pain, Gpr160 is also expressed in patients with neuropathic pain. Indeed, a recent study identified Gpr160 as one of the top pain-associated genes upregulated in the dorsal root ganglion in a cohort of female patients with neuropathic pain who underwent thoracic vertebrectomy surgery for spinal reconstruction or tumor resection.…”
Section: Introductionmentioning
confidence: 99%
“…This causes concerns surrounding the validity of many mechanisms and targets that were identified in older studies that predominantly used male rodents, and raises the question of whether therapeutics that were developed through studies done mostly in one species will translate to another species, much less humans (Mogil, 2016). In a new paper published in British Journal of Pharmacology , Ghazisaeidi and colleagues have taken a comprehensive approach to examining transcriptional changes in the spinal dorsal horn in response to peripheral nerve injury in both sexes in mice and rats (Ghazisaeidi et al, 2023). We think that their experimental design sets a new standard for the field for focusing on pain mechanisms and identifies targets that have the best probability for meaningful clinical translation.…”
mentioning
confidence: 99%